Study of psychological phenomena in the structure of chronic pain: depression, anxiety, catastrophizing. Literature review. - Asanova, Азізе; Mukharovska, Iнна (Psychosomatic Medicine and General Practice, 2023)
Introduction. Chronic pain is associated with a plethora of negative personal and social consequences, including impaired functioning, disability, increased suicidality, and mortality. Modern medicine views pain as a complex phenomenon, and the prevailing biopsychosocial model of disease development allows us to take a broader look at the issue of pain, and thoroughly evaluate all components of the pathological process, thus subsequently reducing the impacts of negative biological, psychological, and social factors. An increasing body of research indicates the growing role of psychological factors such as depression, anxiety, and catastrophizing in influencing the perception, course of pain disorder, as well as the quality of life of patients with chronic pain. However, unfortunately, the significance of psychological factors remains incompletely recognized by patients, and sometimes even by healthcare providers. Objective. The aim of the study was to explore the role of catastrophizing and negative emotions in the structure of chronic pain and, based on the analysis of scientific sources, to select diagnostic methodologies for appropriate screening of these psychological phenomena. Materials. Literature review on the topic. Results. As a result of the analysis of scientific sources, the following methodologies were chosen for studying psychological phenomena in chronic pain. The Pain Catastrophizing Scale (PCS) was selected for studying catastrophic thoughts in patients with chronic pain. The Hospital Anxiety and Depression Scale (HADS) was chosen for screening depression and anxiety. Conclusions. Depression, anxiety, and catastrophizing are potential indicators of an unfavorable prognosis for individuals coping with chronic pain. The combination of these factors may hinder progress in combating inflammatory processes, prolong postoperative rehabilitation periods, worsen overall functioning, and lead to disability. Further exploration of negative impact factors such as depression, anxiety, and catastrophizing promises to reveal new mechanisms for providing personalized pain relief to individuals suffering from chronic pain.